Burden of ventricular arrhythmias at 12-lead 24-hour ambulatory ECG monitoring in middle-aged endurance athletes versus sedentary controls. (December 2018) - Zorzi, Alessandro; Mastella, Giulio; Cipriani, Alberto; Berton, Giampaolo; Del Monte, Alvise; Gusella, Beatrice; Nese, Alberto; Portolan, Leonardo; Sciacca, Federico; Tikvina, Suada; Tollot, Saverio; Trovato, Domenico; et al.
Background: Whether prolonged and intense exercise increases the incidence of ventricular arrhythmias in middle-aged athletes remains to be established. Design: Prospective, case-control. Methods: We studied 134 healthy competitive athletes >30 years old (median age 45 (39–51) years, 83% males) who had been engaged in 9 ± 2 h per week of endurance sports activity (running, cycling, triathlon) for 13 ± 4 consecutive years. One hundred and thirty-four age- and gender-matched individuals served as controls. Both groups underwent 12-lead 24-h ambulatory electrocardiogram monitoring, which included a training session in athletes. Ventricular arrhythmias were evaluated in terms of number, complexity (i.e. couplet, triplet or non-sustained ventricular tachycardia), exercise-inducibility and morphology. Results: Thirty-five (26%) athletes and 31 (23%) controls showed >10 isolated premature ventricular beats or ≥1 complex ventricular arrhythmia ( p = 0.53). Athletes with ventricular arrhythmias were older (median 48 versus 43 years old, p = 0.03) but did not differ with regard to hours of training and years of activity compared with athletes without ventricular arrhythmias. Ten (7%) athletes and six (5%) controls showed >500 premature ventricular beats/24 h ( p = 0.30): the most common ventricular arrhythmia morphologies were infundibular (six athletes and five controls) and fascicular (two athletes and one control). Conclusions: The prevalence of ventricular arrhythmias at 24-hour ambulatory electrocardiogram monitoring did not differ between middle-aged athletes and sedentary controls and was unrelated to the amount and duration of exercise. These findings do not support the hypothesis that endurance sports activity increases the burden of ventricular arrhythmias. Among individuals with frequent premature ventricular beats, the predominant ectopic QRS morphologies were consistent with the idiopathic and benign nature of the arrhythmia.